(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Business might be defined as group of people associated together to achieve a few common objective. A company created and also registered under the Companies Act has particular special features, and they reveal the dynamics of a business. These qualities may also be known as the benefits of an enterprise because as compared with some other business groups, these’re in fact, beneficial for an enterprise. Businesses will be categorized into 5 groups based on the method of incorporation on the foundation of quantity of users, on the basis of command, on the basis of ownership as well as on the basis of nationality of the business.